Budidaya Seabass Asia (Lates calcarifer) di Keramba Jaring Apung di Pusat Pengembangan Budidaya Perairan Air Payau [The Culture of Asian Seabass (Lates calcarifer) in Floating Net Cages at the Brackishwater Aquaculture Development Center] - Fadhliyatud Diniyyah (Faculty of Fisheries and Marine Universitas Airlangga, 2018)
AbstractThis study was carried out to investigate the effect of Asian seabass (Lates calcarifer) culture in floating net cages at the Brackishwater Aquaculture Development Center, Situbondo. Asian seabass were fed with commercial fish pellet (KPA) and fresh fish (trash fish) for 21 days. Seabass fed with trash fish and commercial fish pellet displayed the growth response to the average weight and length. The fish grew from an initial weight of 230g, 238g, and 244g in 21 days and the average length of seabass changed from 23 cm, 25 cm and 28 cm respectively. The fish were fed with 3-7% body weight of fish and the growth was monitored in 21 days. The results showed that trash fish can increase the significant growth response in Asian seabass. AbstrakStudi ini dilaksanakan untuk mengetahui pengaruh budidaya kakap putih Asia (Lates calcarifer) di keramba jarring apung di pusat pengembangan budidaya air payau, Situbondo. Kakap putih Asia diberi pelet ikan komersial (KPA) dengan ikan segar (limbah ikan) selama 21 hari. Kakap putih makan dengan limbah ikan dan pelet ikan komersial menunjukkan respon pertumbuhan rata-rata dari berat dan panjang. Pertumbuhan ikan dari berat awal 230g, 238g dan 244g pada hari ke- 21 dan terjadi perubahan panjang rata-rata kakap putih masing-masing menjadi 23 cm, 25 cm dan 28 cm. Ikan diberi makan dengan 3-7% dari berat badan ikan dan pertumbuhan diamati dalam 21 hari. Hasil penelitian menunjukkan bahwa limbah ikan dapat meningkatkan respon pertumbuhan yang signifikan di kakap putih Asia.